Clinical characteristics, treatment, and treatment switch after molecular-genetic classification in individuals with maturity-onset diabetes of the young: insights from the multicenter real-world DPV registry - Lanzinger, Stefanie; Laubner, Katharina; Warncke, Katharina; Mader, Julia K.; Kummer, Sebastian; Boettcher, Claudia; Biester, Torben; Galler, Angela; Klose, Daniela; Holl, Reinhard W. (Journal of diabetes, 2024)
Background Individuals with maturity-onset diabetes of the young (MODY) are often misdiagnosed as type 1 or type 2 diabetes and receive inappropriate care. We aimed to investigate the characteristics and treatment of all MODY types in a multicenter, real-world setting. Methods Individuals with MODY from the diabetes prospective follow-up (DPV) registry were studied. We compared clinical parameters during the first year of diabetes and the most recent treatment year after MODY diagnosis. Results A total of 1640 individuals were identified with GCK-MODY (n = 941) and HNF1A-MODY (n = 417) as the most frequent types. Among these, 912 individuals were available with information during the first and the most recent treatment year (median duration of follow-up: 4.2 years [2.6-6.6]). Positive beta cell autoantibodies were present in 20.6% (15.2% IAA). Median age at diagnosis ranged from 9.9 years in GCK-MODY (Q1-Q3: 6.2-13.1 years) and INS-MODY (2.7-13.7 years) to 14.3 years (5.0-17.1) in KCNJ11-MODY. Frequency of oral antidiabetic agents (OAD) use increased and insulin decreased in HNF4A-MODY (OAD: 18% to 39%, insulin: 34% to 23%) and in HNF1A-MODY (OAD: 18% to 31%, insulin: 35% to 25%). ABCC8-MODY was characterized by a decrement in nonpharmacological treatment (26% to 16%) and “insulin only” treatment (53% to 42%), while the proportion of individuals treated with OAD but no insulin increased from 0% to 21%. Conclusions Our results indicate that some teams caring for individuals with MODY are hesitant with regard to current recommendations. Registries are an essential source of information and provide a basis for discussing treatment guidelines for MODY.